2011
DOI: 10.15835/nbha3915844
|View full text |Cite
|
Sign up to set email alerts
|

Soil Seed Bank and Aboveground Vegetation in Grazing Lands of Southern Marmara, Turkey

Abstract: The composition and conservation of plant communities is greatly influenced by the soil seed bank. Information on the soil seed banks and the remaining vegetation in these ecosystems is crucial for guiding the restoration efforts. This study examines the size, species richness, diversity, uniformity, and similarity of soil seed banks and aboveground vegetation in 6 different grazing lands including coastal pasture, reseeded pasture, artificial pasture, lowland shrubland, ungrazed pasture, and hillside shrublan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Forbs were the most abundant plants in the SSB composition. In accordance with the results of our study, Bertiller & Ares (2011), Parlak, Gokkus, & Demiray (2011), and Tessema, de Boer, Baars, & Prins (2012 reported that forbs had the highest number of species in SSB. Comparing with the grasses, the higher number of forbs in the AGV might be a reason for increasing the seeds of these species in the SSB.…”
Section: Discussionsupporting
confidence: 92%
“…Forbs were the most abundant plants in the SSB composition. In accordance with the results of our study, Bertiller & Ares (2011), Parlak, Gokkus, & Demiray (2011), and Tessema, de Boer, Baars, & Prins (2012 reported that forbs had the highest number of species in SSB. Comparing with the grasses, the higher number of forbs in the AGV might be a reason for increasing the seeds of these species in the SSB.…”
Section: Discussionsupporting
confidence: 92%
“…The samples were taken by hammering a square metal box frame 40 cm×40 cm into the soil at depth (0-10 cm) (Ghermandi, 2018). The samples of soil seed bank were eliminated from plant fragments and stones and stored in a laboratory room which was dark, cold store (1°C) for 3 months (Özaslan Parlak et al, 2011).…”
Section: Sampling Of Soil Seed Bankmentioning
confidence: 99%